NAY: Opereta Ilustrada. Composición de una opereta a partir de la adaptación de los capítulos XL al XLIII del libro María del autor colombiano Jorge Isaacs, correspondientes a la historia de Nay (2020)
NAY: Opereta Ilustrada is an operetta that adapts chapters XL to XLII from the book Maria by Colombian author Jorge Isaacs. These chapters correspond to Nay’s story; an African princess taken away from her husband, Sinar, her father and her land, brought to the Spanish colony of “Nueva Granada”. This operetta is presented in an audio-visual format, in which the dramatic action is portrayed through lyrical and instrumental music, along with animated illustrations to bring Opera to new formats and audiences. This interdisciplinary project composed and directed by William Sébastian Gomez Veloza, had the participation of Laura Vanessa Bello Martinez (Frognessa) in the illustrations, Nicolas Gomez in montage and edition, Jhonattan Gaviria in sound mixing, Angela Maria Rodriguez Rueda in drama adaptation; along with singers Ana Lucelly Martínez (soprano) as Nay, Ernesto Angulo (bass) as Doctor Mayn, Magmahú and The Missionary, and Carlos Felipe Cerchiaro (baritone) as Sinar and Efraín.